Structural and magnetic properties of superconductive YFeSb<> 1 2 compound - BOYRAZ, CİHAT (My University, 2023)
The structural and magnetic analysis of the YFeSb1.2 compound synthesized by the solid-state reaction method was observed At room temperature, the compound exhibits the ThCr2Si2-Type structure with the space group of I4âmm Low-field DC magnetic susceptibility property of the YFeSb1.2 compound has been examined An obvious oscillation of the remanent magnetization, Mrem(T) with temperature was observed The YFeSb1.2 compound exhibits large irreversibility at low fields below the coercivity fields due to freezing spins at low temperatures At higher temperatures, the susceptibility obeys perfectly to modified Curie-Weiss behavior Each magnetic ion on a microscopic scale and each magnetic cluster on a nanoscale experience reveal a local random anisotropy
Keywords: Fizik; Yoğun Madde 1:Yapısal, Mekanik ve Termal Özellikler; Temel Bilimler; Physics; Condensed Matter 1: Structural, Mechanical and Thermal Properties; Natural Sciences; Temel Bilimler (SCI); FİZİK, YOĞUN MADDE; FİZİK, UYGULAMALI; Natural Sciences (SCI); PHYSICS; PHYSICS, CONDENSED MATTER; PHYSICS, APPLIED; İstatistiksel ve Doğrusal Olmayan Fizik; Fizik Bilimleri; Yoğun Madde Fiziği; Statistical and Nonlinear Physics; Physical Sciences; Condensed Matter Physics; Curie-Weiss behavior; low-field DC magnetic susceptibility; solid-state reaction method; ThCr2Si2-Type structure